1972
DOI: 10.1021/ja00762a032
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high polarizability of hydrogen bonds

Abstract: SCF-MO-LCGO calculations are performed for H502+ as a model illustrating the properties of a symmetrical hydrogen bond with a double-minimum potential well. The potential curves for the proton in the hydrogen bond with and without electrical fields for various 0-0 distances are calculated, along with the dipole moments, polarizabilities, hyperpolarizabilities, and transition moments of the OH stretching vibrations in the hydrogen bond. The total dipole moment is almost twice as large as the contribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(124 citation statements)
references
References 1 publication
7
115
0
Order By: Relevance
“…Scheiner 29 showed that [NHN] bridges behave similarly to [OHO] , which are about 0.1 Å shorter. Janoschek et al 31 showed that of two possible transitions, 0 →0 À , and 0 →1 À , the latter is characterized by a probability that is the lower the higher is the barrier. If the distance between the 0 and 0 À levels is considerable, then we do not observe transitions from the 0 À levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheiner 29 showed that [NHN] bridges behave similarly to [OHO] , which are about 0.1 Å shorter. Janoschek et al 31 showed that of two possible transitions, 0 →0 À , and 0 →1 À , the latter is characterized by a probability that is the lower the higher is the barrier. If the distance between the 0 and 0 À levels is considerable, then we do not observe transitions from the 0 À levels.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in temperature causes an intensification of that band, particularly in the low-frequency wing. As follows from calculation, 31 the transition moment for the 0 →0 À transition is the larger the higher is the barrier. Thus the increase in population of low-lying local levels should lead to an enhancement of the integrated intensity, especially in the low-frequency wing.…”
mentioning
confidence: 80%
“…11, 12, 15a). The polarizability of a hydrogen bond decreases with increasing polarization of the hydrogen bond (13,14 to the local electrical fields in the solution. the external field can no longer polarize the hydrogen bond and induce a preferred direction of the H 5 0 1 structure diffusion.…”
Section: Comparison With Electrochemical Resultsmentioning
confidence: 99%
“…The origin of the b(t) term is the coupling of an external electric field to the transition dipole moment of the tunneling object. In the delocalized basis it has the form [50][51][52] 2b͑t͒ϭm•E͑t͒.…”
Section: ͑21͒mentioning
confidence: 99%